2012
DOI: 10.12735/jbm.v1i1p40
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Productivity of Arab SMEs through Knowledge Management

Abstract: Abstract:Today knowledge is considered to be the primary resource of competitive advantage. This paper analyzed and accessed the status of KM in SMEs in Arab countries. It also examined the factors that influence the adoption of KM for SMEs in the region. In this paper; a comprehensive literature study, a Knowledge Management's personalization approach were undertaken to set a KM Personalization Framework. Many organizations have profited from KM because they recognize the importance of the KM in business grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Furthermore, conclusions drawn from a past studies (Luen & Al-Hawamdeh, 2001;Lahneman, 2004;Hildreth & Kimble, 2004;Hughes & Jackson, 2004;Weir & Hutchings, 2005;Weir & Hutchings, 2006b;Glomseth, Gottschalk, & Solli-Saether, 2007;Mitchell & Casey 2007;Berg et al, 2008;Hashemian & Mahdizane, 2008;Nordin, Pauleen, & Gorman, 2009;Al Rawabdeh, 2009;Tlaiss & Kauser, 2010;Biygautane & Al-Yahya, 2010;Seba & Rowley, 2010;Ajmal, Helo & Kekale, 2010;Bigliardi, Dormio & Galati, 2010;Nour, 2010;Chawla & Joshi, 2011;Chong et al, 2011;Al-Salti & Hackney, 2011;Etter & Griffin 2011;Mohannak, 2011;Randeree & Chaudhry, 2012;Cardoso, Meireles & Ferreira Peralta, 2012;Emine, 2012;Kumar & Che Rose, 2012;Odedait et al, 2012;Seba, Rowley & Delbridge, 2012) indicate that each of these dimensions have a significant influence on KM success and are also interrelated in their effect on KM. For instance, leadership style and organizational culture in Arab organizations are built on the beliefs and values of the national culture and influenced by religion of Islam.…”
Section: Pilot Studymentioning
confidence: 98%
See 3 more Smart Citations
“…Furthermore, conclusions drawn from a past studies (Luen & Al-Hawamdeh, 2001;Lahneman, 2004;Hildreth & Kimble, 2004;Hughes & Jackson, 2004;Weir & Hutchings, 2005;Weir & Hutchings, 2006b;Glomseth, Gottschalk, & Solli-Saether, 2007;Mitchell & Casey 2007;Berg et al, 2008;Hashemian & Mahdizane, 2008;Nordin, Pauleen, & Gorman, 2009;Al Rawabdeh, 2009;Tlaiss & Kauser, 2010;Biygautane & Al-Yahya, 2010;Seba & Rowley, 2010;Ajmal, Helo & Kekale, 2010;Bigliardi, Dormio & Galati, 2010;Nour, 2010;Chawla & Joshi, 2011;Chong et al, 2011;Al-Salti & Hackney, 2011;Etter & Griffin 2011;Mohannak, 2011;Randeree & Chaudhry, 2012;Cardoso, Meireles & Ferreira Peralta, 2012;Emine, 2012;Kumar & Che Rose, 2012;Odedait et al, 2012;Seba, Rowley & Delbridge, 2012) indicate that each of these dimensions have a significant influence on KM success and are also interrelated in their effect on KM. For instance, leadership style and organizational culture in Arab organizations are built on the beliefs and values of the national culture and influenced by religion of Islam.…”
Section: Pilot Studymentioning
confidence: 98%
“…The findings of Kumar and Che Rose (2012) imply that organizations in the public sector should have a clear understanding of the effects of the IWE on the conduct of employees. Emine (2012) investigated the impact of KM on the productivity of small and medium enterprises (SMEs) in the Arab world and found that many organizations in the Arab world recognize the contribution of knowledge to their competitiveness. However, it was also found that many other Arab SMEs have not realised the importance of KM.…”
Section: Past Studies and The Research Gapmentioning
confidence: 99%
See 2 more Smart Citations
“…There are more than 10 million firms under the category of SMEs and contributions in GDP are 35%. This indicates that the vital role of SMEs in the economic growth of Arab countries; accordingly Arab nations have recognized the importance of SMEs and have formulated policies to encourage, support, and fund them [Emine, 2012].…”
Section: Introductionmentioning
confidence: 99%